1981
DOI: 10.1364/ao.20.000430
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of stress-induced changes in the transverse refractive-index profile of optical fibers

Abstract: Changes in transverse refractive index induced by the photoelastic effect are calculated when an optical fiber is subjected to a uniformly applied diametral stress. For moderate values of the force per unit length applied to the fiber, we find that regions of comparable or higher refractive index than the core may be induced in the outer region of the fiber. Thus the stressed region is capable of acting as a mode converter that affects the transmission characteristics of the fiber and may enable coupling of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1982
1982
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…The additional possibility of transverse strain measurement is introduced by the action of a transverse load when the refractive-index profile of a fiber is modified to induce birefringence. 1,2 Fiber sensors capable of measuring transverse loads can open up new possibilities in multiaxis load sensing, for example, to investigate the strain field in composite materials 3,4 or as all-fiber alternatives to load cells for engineering and process applications requiring compact sensors for hazardous environments.…”
Section: Introductionmentioning
confidence: 99%
“…The additional possibility of transverse strain measurement is introduced by the action of a transverse load when the refractive-index profile of a fiber is modified to induce birefringence. 1,2 Fiber sensors capable of measuring transverse loads can open up new possibilities in multiaxis load sensing, for example, to investigate the strain field in composite materials 3,4 or as all-fiber alternatives to load cells for engineering and process applications requiring compact sensors for hazardous environments.…”
Section: Introductionmentioning
confidence: 99%
“…The stress f ield in transversely loaded f iber was originally investigated to estimate possible mode coupling effects arising from transverse stress perturbations of the refractive-index prof ile. 2 This was followed by studies of the birefringence induced by transverse stresses that were due to external load 3 or internal thermally induced stresses in highly birefringent (hi-bi) fiber. 4,5 The response of FBGs in hi-bi f iber to transverse loading was reported by Lawrence et al, 1 who showed that the Bragg wavelength shifts corresponding to the two orthogonal polarization modes varied approximately linearly with transverse load.…”
mentioning
confidence: 99%
“…The stress distribution along the X-axis and Y-axis at any point (x, y) for a lateral load P acting over a length L is given by [84,85,86] (T…”
Section: Theorymentioning
confidence: 99%
“…The refractive index gradient at any point P (x, y, z) in the grating is related to the stress distribution by the following equations [84,85,86] for X polarization,…”
Section: Refractive Index Modulationmentioning
confidence: 99%
See 1 more Smart Citation